Media Trainer Kit To Improve Students' Independence And Understanding In Practical Learning - S, Moh. Arif Rohman; Rohmah, Ana Qaimah Lailiyatul Mela Diyah; Cholilah, Cholilah; Kusmiyati, Kusmiyati; Muhajir, Muhajir (Lembaga Riset dan Inovasi Almatani, 2024)
The development of science and technology (Science and Technology) has an impact on all aspects of life. In addition to rapid development, changes are also happening rapidly. Therefore, humans need to adapt to obtain, manage and utilize science and technology (Science and Technology) proportionally. One of the media that can be used is the KIT media trainer. Trainer Kit is a tool (object) used to demonstrate certain facts, concepts, principles or procedures to make it look more real / concrete so that it can make it easier for students to understand the material taught. The results of this study are expected to contribute to the benefits of KIT media trainers. This type of research is a literature study, researchers review several articles and books related to KIT trainet media in their contribution to increasing student independence and understanding.